Video games, violence, and the ethics of fantasy : killing time - Bartel, Christopher (London [England] : Bloomsbury Academic, 2020)
"Is it ever morally wrong to enjoy fantasizing about immoral things? Many video games allow players to commit numerous violent and immoral acts. But, should players worry about the morality of their virtual actions? A common argument is that games offer merely the virtual representation of violence. No one is actually harmed by committing a violent act in a game. So, it cannot be morally wrong to perform such acts. While this is an intuitive argument, it does not resolve the issue. Focusing on why individual players are motivated to entertain immoral and violent fantasies, Video Games, Violence, and the Ethics of Fantasy advances debates about the ethical criticism of art, not only by shining light on the interesting and under-examined case of virtual fantasies, but also by its novel application of a virtue ethical account. Video games are works of fiction that enable players to entertain a fantasy. So, a full understanding of the ethical criticism of video games must focus attention on why individual players are motivated to entertain immoral and violent fantasies. Video Games, Violence, and the Ethics of Fantasy engages with debates and critical discussions of games in both the popular media and recent work in philosophy, psychology, media studies, and game studies."--
1. Introduction: The Problem of Virtual Ethics -- 2. Amoralist Avoidance Strategies: Fiction and Games -- 3. Virtual Ethics and Virtue Ethics -- 4. Free Will, Motivation, and the Limits of Moral Criticism -- 5. Virtual Immoral Fantasies -- 6. Virtue Ethics on the Gamer's Dilemma -- 7. Criticizing Games -- Bibliography -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Video games -- Moral and ethical aspects; Video games -- Philosophy; Philosophy: aesthetics; Electronic books